Evaluation of Promotive and Preventive Strategies in Control Non Communicable Diseases (NCDS) in Indonesia - Ariska Agustina; Kartika Destya Arini; Evi Kusumastuti; Setianingrum; Didin Sunardi; Prima Paramita Putri; Budi Hartono (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Non- communicable diseases (NCDs) have be one of challenge health public the largest in Indonesia and the world, along with with transition epidemiology , changes pattern consumption , style life sedentary , and aging population. Increasing prevalence of diabetes mellitus , hypertension , disease cardiovascular disease​ lungs chronic and cancer demand strengthening promotive and preventive strategies as approach main in PTM control. However,the implementation various promotive and preventive programs often more​ oriented towards achieving administrative output compared to change behavior and impact measurable health ,so that need systematic, comprehensive ,and ongoing strategy evaluation .This article aim For study in a way conceptual evaluation of promotive and preventive strategies in PTM control ,including concept and urgency evaluation , principles health strategy evaluation ,relevant evaluation models and learning from studies case national and global. The methods used is approach conceptual through synthesis literature key in the field health strategy evaluation and analysis reflective to studies case implementation policy health . Study results show that effectiveness of promotive and preventive strategies No only determined by the scope of the program, but is greatly influenced by the relevance intervention with need society , quality implementation , capacity source Power human resources , availability of valid data, and governance and coordination cross sector . This article emphasize importance implementation principle evaluation based evidence , participatory , fair , efficient , and sustainable , as well as evaluation model integration such as Logic Model, CIPP, Donabedian, and Balanced Scorecard in cycle policy health . Findings This implies the need for strengthening monitoring and evaluation system , improvement evaluator capacity , as well as shift orientation evaluation from just output achievement towards measurement of health outcomes and impacts public.